Pendekatan Astronomis dalam Studi Islam - Siti Mufarokah; Nurul Al Fudiah; Septia Solihati; Sabrur Rahma; Zulfi Mubaraq (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims to determine whether or not the effect of profitability, liquidity and solvency on Islamic stock returns, the effect of profitability, liquidity and solvency on investment risk, the effect of investment risk on Islamic stock returns and whether or not significant investment risk as an intervening variable mediates the effect of profitability, liquidity and solvency on sharia stock returns. By using a sample of companies whose shares are listed on the Jakarta Islamic Index (JII) for the 2016-2021 period and multiple panel data regression with the best Common Effect Model (CEM) model, the following results are obtained: profitability, liquidity and solvency have a significant positive effect on Islamic stock returns; profitability, liquidity and solvency have a significant positive effect on investment risk; investment risk has a significant positive effect on sharia stock returns; and investment risk as an intervening variable has a significant positive effect mediating the effect of profitability, liquidity and solvency on sharia stock returns.